Muzyka jako narzędzie kształtowania myślenia matematycznego w edukacji dzieci = Music as a tool for the shaping of mathematical thinking in the primary education - Łuczak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article consists of the analyses concerning the possibilities of connecting teaching mathematics and music in the preschool and the elementary education. The author presented the role of the musical education in the upbringing and the shaping of the children?s characters. This type of education is directed not only on the musical development of the child, but it also influences its intellectual, physical and social development. As it was indicated in the text there are the possibilities of the implementation of music in the shaping of the given mathematical notions.
Keywords: dziecko; edukacja; nauczanie; matematyka; muzyka; kształcenie zintegrowane; child; education; teaching; mathematics; music; integrated education